2021
DOI: 10.29333/ejgm/9695
|View full text |Cite
|
Sign up to set email alerts
|

The Cumulative Impact of Sarcopenia, Frailty, Malnutrition, and Cachexia on Other Geriatric Syndromes in Hospitalized Elderly

Abstract: Background: Sarcopenia, frailty, malnutrition, and cachexia are overlapping conditions in hospitalized older adults; they are characterized by altered body composition and are associated with poor outcomes. Aim: to quantify the effect of this overlap on other geriatric giants e.g., delirium, cognitive impairment, and functional disability in hospitalized older adults. Methods: A cross sectional observational study involving 206 hospitalized older adults was conducted. Each patient was assessed using Arabic val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
17

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 46 publications
0
9
0
17
Order By: Relevance
“…Its evaluation shows the severity of processes that the individual may be suffering in the decline of their functional capacities 18,25 . This multifactorial character of decline is identified in the studies of this review, in which low rates in BADL were revealed 18,20,21,25,27 .…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Its evaluation shows the severity of processes that the individual may be suffering in the decline of their functional capacities 18,25 . This multifactorial character of decline is identified in the studies of this review, in which low rates in BADL were revealed 18,20,21,25,27 .…”
Section: Discussionmentioning
confidence: 67%
“…From the analysis of the articles chosen for this study, the main instruments for the evaluation of each domain were identified. Regarding functional capacity, the most used instruments were Katz Index 18,[20][21]25,27 , Lawton, and Brody Index 18,[20][21][22]26,28 , and Barthel Index 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sousa-Santos et al found a frequency of 2.2% of coexistence of these conditions in a sample of community-dwelling Portuguese older adults ( n = 1454, age ≥ 65 years) [ 25 ]. Rasheedy & EL-Kawaly reported an overlap of 25.3% of frailty and sarcopenia in a sample of 206 hospitalized Egyptian patients with ages ≥ 60 years and with multiple comorbidities and diseases, including 21.4% of HF patients who were not stratified for the co-occurrence [ 26 ]. Both these studies used the same assessment methods (Fried et al and EWGSOP2) for classifying frailty and sarcopenia as the present work.…”
Section: Discussionmentioning
confidence: 99%